Microbial network stability is linked to soil multifunctionality and functional trade-offs under long-term fertilization in a dryland agroecosystem - Fangfang Li; Xihe Wang; Yaping Huang; Xin Li; Lei Wu; Jinyu Yang; Wanli Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2027)

Micro/nanoscale biochar facilitates cadmium immobilization and soybean resilience: Insights from microbial life-history strategies and plant physiological response - Yaping Wang; Yichen Xu; Yini Cao; Yi Hu; Changrui Liu; Chuanxin Ma; Wende Yan (Bioresource Technology, 2026)

Orbital-hybridized electron bridge enables functional compartmentalization for ultradeep electrosorption - Bijie Bie; Xiaodong Xie; Shuncai Luo; Qingtan Xu; Song Xie; Yaping Miao; Xuming Zhang; Biao Gao; Zhaobo Wang; Buxiao Kuang; Fang Zhou; Liwei Xiong; et al. (Chemical Engineering Journal, 2026)

Optimizing organic resource allocation to enhance microbial necromass nitrogen accrual: Evidence from multiple long-term fertilization experiments - Jun Wang; Yaping Huang; Qiong Xiao; Dong Wu; Dongchu Li; Xin Li; Lei Wu; Yinghua Duan; Minggang Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2026)

Optimizing Holstein bovine oocyte development: Evidence-Based donor selection for OPU-IVP - Heqiang Li; Baobao Zhao; Jingya Wang; Xuexiao Song; Jieyu Wang; Yang Li; Zihan Xu; Zheng Wang; Yaochang Wei; Zhuangsheng Wang; Yaping Jin; Yongsheng Wang (Theriogenology, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

A fast-response framework for real-time 3D wind field reconstruction: Supporting urban air mobility applications in complex environments - Zihao Pang; Junxia Gu; Quanqian Xu; Shuai Han; Lanxin Luo; Zhiqiang Zhang; Zhi Zhu; Tao Zhang; Yaping Ma; Dongdong Shen (Sustainable Cities and Society, 2026)

Exercise-induced neuropeptidergic and neurochemical neuroadaptation in stress regulation and emotional disorders - Ziqi Wang; Zhinei Tan; Yaping Zhang; Yuzhou Li; Jinyan Lin; Yingli Xu; Yongxia Li; Ting Chen (Acta Neurologica Belgica, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Metabolic engineering of Dunaliella salina enhances astaxanthin production: combined effects of heterologous enzyme co-expression and dual-stress optimization - Hao Zhang; Yifan Kong; Yaping Shao; Ziqi Zhang; Celong Zhao; Fuhao Xu; Fenglin Yang; Fengjie Sun; Yulin Cui; Yuyong Wu; Chunxiao Meng; Zhengquan Gao (World Journal of Microbiology and Biotechnology, 2026)

In situ generation of NKG2D CAR T/NK cells via a tumor-targeted lipoplex for enhancing cancer immunotherapy - Xiaoxuan Xu; Wenzhe Yi; Xiangshi Sun; Zhiwen Zhao; Jialin Duan; Ting Wu; Xiaoting Shan; Jie Li; Dangge Wang; Yaping Li (Science Bulletin, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Performance optimization and application advances of cellulose-based triboelectric materials for high-humidity environments - Yakun Mou; Yuhang Qiu; Mingyang Li; Yaping Zeng; Yanniu Xu; Dengjun Lu (Carbohydrate Polymers, 2026)

Numerical study on the icing hazard zone of engine intake components under anti-icing conditions - Shuliang Jing; Yaping Hu; Jing Xu; Yuetao Jiang; Weiliang Zheng; Yaxin Du (Cold Regions Science and Technology, 2026)

Large-scale farming enhances soil health in contrast to smallholder management: Insights from a field survey - Xin LI; Dong WU; Yaping HUANG; Xiao YANG; Gilles COLINET; Caroline DE CLERCK; Wenju ZHANG; Minggang XU; Jeroen MEERSMANS (Pedosphere, 2026)

Seawater acidification accelerates growth but hastens decline in batch cultures of the marine diatom Thalassiosira pseudonana - Haiyang Zong; Zihao Sun; Dongmei Lv; Yu Shang; Yaping Wu; Juntian Xu; Futian Li (Marine Environmental Research, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

HSF-1 Regulates Autophagy to Govern Motor Function and Facilitate Toxic Protein Clearance in a C. elegans Model of Amyotrophic Lateral Sclerosis - Hui Xu; Yaping Shao; Jun Zhang; Yang Ni; Guowang Xu; Cong Liu; Yi Liang; Weidong Le (Neuroscience Bulletin, 2026)

Long-term fertilization-induced increases in glomalin-related soil protein depend on phosphorus input and aggregate stability across climatic zones - Hongbo Yang; Guanmo Li; Dong Wu; Qiong Xiao; Xin Li; Yaping Huang; Jeroen Meersmans; Gilles Colinet; Minggang Xu; Wenju Zhang (Soil and Tillage Research, 2026)

Reconstructing all-weather remotely sensed air temperature via a kernel-based temporal filling and bias correction (KTF-BC) framework - Yan Xin; Yongming Xu; Xudong Tong; Meng Ji; Yaping Mo; Yonghong Liu; Shanyou Zhu (Remote Sensing of Environment, 2026)

Synchrony of prehistoric agricultural evolution and drought events in the North China Plain - Yanpeng Li; Shengrui Li; Hai Xu; Keliang Zhao; Guanhan Chen; Yaping Zhang; Jiacheng Ma; Junchi Liu; Yong Ge; Yan Zheng; Xinying Zhou; Xiaoqiang Li (Quaternary Science Reviews, 2026)

Urban land surface temperature prediction by integrating LSTM and geospatial information: A case study of Kunming, China - Ronghui Li; Yaping Zhang; Xu Chen (Journal of Cleaner Production, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

Effects of thermal alkaline hydrolysis and biochar addition on anaerobic digestion of sewage sludge and fate of antibiotic resistance genes - Ruoxin Li; Chunsheng Qiu; Xu Chen; Nannan Liu; Yaping Zhang; Li Qi; Shaopo Wang (Bioresource Technology, 2026)

Life-course body shape trajectories and cerebral oxygen metabolism in community-dwelling older adults - Yifan Yan; Yaping Zhang; Xuhao Zhao; Renwei Chen; Shenghao Fang; Yi Zhou; Jingkai Huang; Fuyan Wang; Christopher Chen; Zixuan Lin; Xin Xu (GeroScience, 2026)
Obesity and lifelong body-shape fluctuation are associated with late-life structural brain damage, suggesting the involvement of metabolic pathways. The cerebral metabolic rate of oxygen (CMRO₂) reflects hemodynamic and oxidative stress and precedes structural atrophy, but its role in adiposity-related brain change remains unclear. We examined whether current and life-course adiposity relate to CMRO₂ and to structural change. A total of 303 community-dwelling adults aged 50 years and older were included. Body shape was assessed using Body Mass Index (BMI) and Body Roundness Index (BRI). Global CMRO₂ was derived from TRUST and phase-contrast MRI. T1-weighted MPRAGE provided volumetry, and medial temporal atrophy (MTA) grading. General linear models estimated associations of BMI and BRI with CMRO₂, including age interactions. Age-stratified mediation tested CMRO₂ as a mediator of adiposity to MTA associations. Body-shape trajectories at ages 25, 40, 60, and current age were modeled and related to CMRO₂ and metabolism-related regions. Adiposity was associated with lower CMRO₂: with overweight (β = -1.12 μmol/100 g/min, 95%CI = (-1.96, -0.28)) and higher BRI (β = -1.31, 95%CI = (-2.36, -0.27)) showing stronger effects with advancing age. Among participants aged 70 years, CMRO₂ mediated the association between BMI and MTA (indirect β = 0.06, 95%CI = (0.01, 0.14)). Three adulthood body-shape patterns emerged, and CMRO₂ was lower in moderate increasing (β = -11.40; 95%CI = (-20.90, -1.90)) and high-rising (β = − 12.23; 95%CI = (-23.56, -0.90)) groups. Metabolism-related regions were larger in higher-risk patterns, particularly the left hypothalamus. Greater and prolonged adiposity is linked to reduced CMRO₂ and related structural differences in older adults.

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Triazine herbicides inhibit phytoplankton photosynthesis in the East China Sea: A species-specific assessment - Yaping Wu; Xiangyu Li; Peijian Ding; Huifang Li; Juntian Xu (Marine Environmental Research, 2026)

Carbonic anhydrase modulates photosynthetic responses to UV radiation in diatoms across temperature gradients - Xiangyu Li; Yuheng An; Juntian Xu; Yaping Wu; John Beardall (Journal of Photochemistry and Photobiology B: Biology, 2026)

Beyond static imaging: A dynamic decision paradigm for robust array-SAR in diverse sensing scenarios - Xiangdong Ma; Xu Zhan; Xiaoling Zhang; Yaping Wang; Jun Shi; Shunjun Wei; Tianjiao Zeng (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Biogenic amines in fermented foods: A comprehensive review from formation pathways, risk analysis, detection technologies to control measures - Yaping Wang; Bing Yan; Haiqian Xu; Yanyan Huang; Qinglin Sheng; Lang-Hong Wang (Food Research International, 2026)

Effect of thermal alkaline and thermal hydrolysis on the methane production and antibiotic resistance genes removal during sewage sludge anaerobic digestion - Ruoxin Li; Chunsheng Qiu; Nannan Liu; Wen Zhang; Xu Chen; Yaping Zhang; Chenchen Wang; Shaopo Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Lanthanide-based MOFs with metal-node-modulated energy transfer for multifunctional X-ray imaging platforms - Chenrui Wang; Haitao Li; Jiankun Xue; Yaping Chen; Lian Wang; Xieming Xu; Shuaihua Wang; Rong Li (Chemical Engineering Journal, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Exploring the potential of UAV-based thermal imagery for monitoring diurnal variations in the microscale urban thermal environment - Meng Ji; Yongming Xu; Shanyou Zhu; Yang Zhang; Yan Xin; Yaping Mo (Energy and Buildings, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans” [Plant Sci. 357 (2025), 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans“ [Plant Sci. 357 (2025) 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Enhanced degradation of 1,2,4-trichlorobenzene by Pd-loaded biochar-supported nZVI: Through a reduction-oxidation coupling process - Wenxuan Luo; Chenghua Xu; Chao Wang; Dandan Yu; Yaping Zhang; Changsheng Qu (Journal of Environmental Management, 2025)

Materials design and mechanistic insights for advancing marine oil spill cleanup by photothermal absorbents - Yaping Wang; Ruixiang Xu; Mohamed Mahmoud Nasef (Journal of Environmental Management, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Research progress on properties and applications of triboelectric nanogenerators based on cellulosic triboelectric aerogels - Yuhang Qiu; Yakun Mou; Xunxiao Wu; Yaping Zeng; Yanniu Xu; Mingyang Li; Dengjun Lu (Chemical Engineering Journal, 2025)

The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Structural remodeling of UiO-66(Ce) into oxygen vacancy defect-rich CeO2: Enhancing selective adsorption of As(III) - Tao Zhang; Xu Tang; Jing Xing; Huan Xu; Ruyu Yan; Yaping Zhao (Journal of Hazardous Materials, 2025)

Assessing Fluoride Contamination in Groundwater of Informal Landfills in the Yangtze River Delta: Implications for Environmental Security and Sustainable Resource Management - Lichen Liang; Xiaofei Yan; Yaping Qi; Lili Wang; Haifeng Tu; Hao Jiang; Dan Wang; Houhu Zhang; Yuanshun Xu (Water, Air, & Soil Pollution, 2025)

Progress on the mechanism of natural polysaccharides in the treatment of arthritis - Lili Yuan; Michael Adu-Frimpong; Hong Chen; Yaping Yang; Jiangnan Yu; Huiya Wang; Yuxiang He; Elmurat Toreniyazov; Xia Cao; Qilong Wang; Ximing Xu (Inflammopharmacology, 2025)

Self-adapting deflection contact effect for rock fracture deformation - Haichun Ma; Yanan Wang; Yang Xu; Jiazhong Qian; Yaping Deng (Acta Geophysica, 2025)

Eutrophication mitigates Cu-induced inhibition on growth and photosynthetic performance in the marine diatom Thalassiosira weissflogii - Shumin Zeng; Xiangyu Li; Linrong Peng; Juntian Xu; Zhenzhen Li; Yaping Wu (Marine Pollution Bulletin, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

Electrochemical enhancement of the accumulation of photosensitive components in anoxygenic phototrophic bacteria extracellular: A new insight into the preparation of degradable microbial photosensitizer for water treatment - Ronghui He; Jian Sun; Yong Yuan; Xiaoyan Bai; Qintie Lin; Yaping Zhang; Kang Dai; Zhenbo Xu (Journal of Hazardous Materials, 2025)

Impact of vacuum treatment on multi-layered structure and physicochemical properties of reconstituted fish steaks: Specific effects of air distribution within meat-air systems - Yaping Fu; Yanshun Xu (Journal of Food Engineering, 2025)

Enhancing cardiac regeneration: direct reprogramming of fibroblasts into myocardial-like cells using extracellular vesicles secreted by cardiomyocytes - Yao Yao; Yuexin Yu; Yaping Xu; Yingtian Liu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

Variation in Biomass Yield and Cell Wall Composition in Switchgrass Natural Variants Under Two Nitrogen Regimes - Mitra Mazarei; Anne E. Harman-Ware; Thomas H. Pendergast; Vivek Shrestha; Yaping Xu; Cristiano Piasecki; Reginald J. Millwood; Katrien M. Devos; C. Neal Stewart (BioEnergy Research, 2025)

Hydrogels in cardiac tissue engineering: application and challenges - Yaping Xu; Yuexin Yu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

Impact of Drought on Farmers’ Livelihood Vulnerability: A Case Study of County-level Units in Western Jilin Province, China - Jiani Zhang; Yang Han; Yangang Fang; Yaping Xu; Chunlin Chen; Zhuxin Liu; Feiyu Wang; Lijuan Zhuang; Fang Huang (Chinese Geographical Science, 2025)

Spatio-temporal variations of heat extremes across the yangtze river delta during 2001–2023 based on remotely sensed seamless air temperature - Chenlu Xu; Yongming Xu; Yaping Mo; Meng Ji; Yonghong Liu; Shanyou Zhu (Environmental Research, 2025)

Hyaluronan-decorated CuO2-doxorubicin nanodot clusters for targetedly sensitizing cuproptosis in breast cancer via a three-pronged strategy - Junmin Qian; Abdalrheem Jarelnaby Musa Aldai; Weijun Xu; Taibing Wang; Kunkun Zhao; Yaping Wang; Jingjing Fan; Aili Suo (Carbohydrate Polymers, 2025)

Online SFE-SFC-MS/MS analysis of pyraclostrobin and chiral mefentrifluconazole residues in mango and mango juice - Hao Yang; Yue Geng; Shu Lin; Lu Wang; Yi Peng; Yaping Xu; Wei Jing; Jing Wei; Zeying He; Xiaowei Liu (Food Chemistry, 2025)

Comparative study of different pretreatment methods on peanut oil quality characteristics, anti-oxidation attributes, and phenolic compound compositions - Mingfei Hao; Yaping Lv; Yuanyi Xiong; Yuanfa Liu; Yong-Jiang Xu; Zhan Ye (Food Chemistry, 2025)

Associations Between Organophosphate Esters Exposure and Metabolic Syndrome: Exploring the Mediating Role of Oxidative Stress and Inflammation in Adults - Sijie Yang; Yaping Li; Ling Liu; Zhengce Wan; Qitong Xu; Chang Xie; Lulu Song; Youjie Wang; Hui Chen; Surong Mei (Exposure and Health, 2025)

Analysis of Common Genetic Variation of Anxiety Disorders in Essential Tremor - Yaping Yan; Lanxiao Cao; Luyan Gu; Congying Xu; Jinyu Lu; Dayao Lv; Jun Tian; Xinzhen Yin; Jiali Pu; Baorong Zhang; Guohua Zhao (Journal of Molecular Neuroscience, 2025)

A hybrid mechanism-based and data-driven model for efficient indoor temperature distribution prediction with transfer learning - Yaping Liu; Jiang Wu; Zhanbo Xu; Yuanjun Shen; Xiaohong Guan (Energy and Buildings, 2025)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

Seasonal relative humidity recorded in tree-ring earlywood and latewood δ18O in the West Tianmu Mountains, southeastern China - Hui Wang; Yaping Zhang; Congcong Xiao; Shiyuan Shi; Jiarui Xu; Michael E. Meadows; Jiangfeng Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

One-step synthesis of iron and carbon-quantum-dot co-decorated graphitic carbon nitride photocatalysts for carbamazepine degradation - Xiaoli Liu; Yaping Wang; Yutao Xie; Tiefeng Xu; Yan Gu; Wangyang Lu (Journal of Environmental Chemical Engineering, 2024)

Biochanin A Attenuates Psoriasiform Inflammation by Regulating Nrf2/HO-1 Pathway Activation and Attenuating Inflammatory Signalling - Yaping Lv; Yingsheng Xu; Songchun Liu; Xianjing Zeng; Bin Yang (Cell Biochemistry and Biophysics, 2024)

Effects of LAZY family genes on shoot gravitropism in Lotus japonicus - Shaoming Xu; Shusi Song; Huawu Jiang; Guojiang Wu; Yaping Chen (Plant Science, 2024)

Porous liquids based on UiO-66@SiO2 through the strategy of growing an ultrathin silica layer for CO2 selective separation - Zhaodi Wang; Yangyang Xin; Wendi Fan; Zheng Dong; Dechao Wang; Yaping Zheng; Yahong Xu (Chemical Engineering Journal, 2024)

Multi-omics analysis reveals anthocyanin synthesis is associated with drought stress tolerance in Chaenomeles speciosa flowers - Shuangyu Zhang; Xiling Chen; Yanshen Ren; Xingyue Xue; Yaping Xu; Qi Wang; Yanru Xie; Tengxun Zhang; Jiayi Lin; Xiaolu Chen; Houhua Li (Journal of Cleaner Production, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Effect of maternal cigarette smoke exposure on COPD progression in offspring mice - Jiawei Sun; Huan Chen; Xu Xu; Yaping Dou; Baofa Wu; Hongyang Zhang; Song Shang; Wuzhuang Sun (Reproductive Toxicology, 2024)

Seasonal dynamics, tidal influences, and anthropogenic impacts on microplastic distribution in the Yangtze River estuary: A comprehensive characterization and comparative analysis - Panfeng Wu; Yuchuan Fan; Xinxin Zhang; Wei Wu; Zaifeng Zhang; Yaping Wu; Jingyi Wang; Jing Xu; Tianming Chen; Bin Gao (Journal of Hazardous Materials, 2024)

Fabric structure and polymer composition as key contributors to micro(nano)plastic contamination in face masks - Shuai Tang; Qun Zhang; Haowen Xu; Mengyuan Zhu; Md. Nahid Pervez; Bing Wu; Yaping Zhao (Journal of Hazardous Materials, 2024)

Effect of Fe2+-activated persulfate combined with biodegradation in removing gasoline BTX from karst groundwater: A box-column experimental study - Yaping Jiang; Renqian Lu; Yudao Chen; Ritian Deng; Xu Deng (Environmental Science and Pollution Research, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

Individual and joint effects of organophosphate esters and hypertension or diabetes on renal injury among Chinese adults - Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Chang Xie; Zhengce Wan; Lulu Song; Yongman Lv; Youjie Wang; Hui Chen; Surong Mei (International Journal of Hygiene and Environmental Health, 2024)

Multi-layered structure and physicochemical properties of reconstituted meat-based products from minced fish by physical extrusion: Impact of extrusion strength - Yaping Fu; Yanshun Xu (Food Research International, 2024)

Well-cushioned and highly-elastic aerogel for multifunctional intelligent transportation packaging - Ruiming Liu; Xiaosen Pan; Zijun Mao; Zijun Xu; Yaping Zhu; Pan Xue; Zhengjian Zhang; Hongbin Liu; Yang Liu; Bowen Cheng (Chemical Engineering Journal, 2024)

Evaluating warming trend over the tibetan plateau based on remotely sensed air temperature from 2001 to 2020 - Yan Xin; Yongming Xu; Xudong Tong; Yaping Mo; Yonghong Liu; Shanyou Zhu (Climatic Change, 2024)

Association between organophosphate esters individual and mixed exposure with the risk of hyperlipidemia and serum lipid levels among adults in Wuhan, China - Qitong Xu; Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Zhengce Wan; Lulu Song; Yongman Lv; Hui Chen; Youjie Wang; Surong Mei (Environmental Science and Pollution Research, 2024)

Associations of exposure to organochlorine pesticides and polychlorinated biphenyls with chronic kidney disease among adults: the modifying effects of lifestyle - Chang Xie; Sijie Yang; Yaping Li; Mingye Zhang; Qitong Xu; Zhengce Wan; Lulu Song; Yongman Lv; Dan Luo; Qiang Li; Youjie Wang; Hui Chen; et al. (Environmental Science and Pollution Research, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Sediment resuspension and transport in the offshore subaqueous Yangtze Delta during winter storms - Min Tian; Haifei Yang; Wenxiang Zhang; Kehui Xu; Benwei Shi; Yaping Wang; Shilun Yang (Frontiers in Marine Science, 2024)
Storm-induced episodic sediment redistribution in coastal systems can reshape geomorphic bodies, disrupt ecosystems, and cause economic damage. However, cold-wave-storm-induced hydrodynamic changes and residual sediment transport in large, exposed subaqueous deltas, such as the Yangtze Delta, are poorly understood because it is typically expensive and difficult to obtain systematic field data in open coast settings during storm events. We conducted a successful field survey of waves, currents, changes in water depth, and turbidity at a station (time-averaged water depth of 20 m) in the offshore subaqueous Yangtze Delta over 10 days during winter, covering two storms and two fair-weather periods. During the storm events, strong northerly winds drove southward longshore currents (~0.2 m/s) and resulted in increased wave height and sediment resuspension, thereby leading to massive southward sediment transport. In contrast, both southward and northward transports were limited during the fair-weather periods. A better understanding of the storm-induced sediment transport can be obtained by using an approximately half-day lag in sediment transport behind wind force, given the time needed to form waves and longshore drift, the inertia of water motion, and the slow settling velocity of fine-grained sediment. Our results directly support previous findings of southward sediment transport from the Yangtze Delta during winter, which is deposited in the Zhejiang–Fujian mud belt in the inner shelf of the East China Sea. In addition, the southward sediment transport from the Yangtze Delta occurs mainly during episodic storm events, rather than during the winter monsoon, and winter storms dominate over typhoons in driving southward sediment transport from the delta. This study highlights the importance of storms, especially during winter storms, in coastal sediment redistribution, which is of particular significance when considering the projected increase in storm intensity with global warming.

Revelation of HCl poisoning and enhancement mechanism on N-modified Al2O3 catalysts for COS and CS2 hydrolysis - Peng Wu; Yaping Zhang; Yun Xu; Bingran Wang; Kai Shen; Ke Zhuang; Sheng Wang; Shule Zhang; Shipeng Ding (Fuel, 2024)

Super absorbent resilience antibacterial aerogel with curcumin for fresh pork preservation - Fangqu Wang; Zipeng Xu; Lin Chen; Ziyan Qiao; Yayun Hu; Xiaojing Fan; Yaping Liu; Zhuangli Kang; Feng Huang; Minyi Han; Huijuan Yang; Xianchao Feng (Food Control, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Efficient biostimulation of microbial dechlorination of polychlorinated biphenyls by acetate and lactate under nitrate reducing conditions: Insights into dechlorination pathways and functional genes - Yan Xu; Ying Wang; An Zheng; Yaping Yuan; Lei Xu; Yanqiang Tang; Qingdong Qin (Journal of Hazardous Materials, 2024)

Photochemical behaviors of sludge extracellular polymeric substances from bio-treated effluents towards antibiotic degradation: Distinguish the main photosensitive active component and its environmental implication - Xuexian Zhong; Jian Sun; Yong Yuan; Yaping Zhang; Xiaoyan Bai; Qintie Lin; Kang Dai; Zhenbo Xu (Journal of Hazardous Materials, 2024)

A novel alginate-embedded magnetic biochar-anoxygenic photosynthetic bacteria composite microspheres for multipollutant removal: Mechanisms of photo-bioelectrochemical enhancement and excellent reusability performance - Ronghui He; Jian Sun; Xiaoyan Bai; Qintie Lin; Yong Yuan; Yaping Zhang; Kang Dai; Zhenbo Xu (Environmental Research, 2024)

Optical sensors of volatile organic compounds for non-invasive diagnosis of diseases - Xiaoyun Qu; Yaping Hu; Chenggang Xu; Yue Li; Lin Zhang; Qiao Huang; Sareh Sadat Moshirian-Farahi; Jianmin Zhang; Xiahong Xu; Ming Liao; Yingchun Fu (Chemical Engineering Journal, 2024)

Long-term liming mitigates the positive responses of soil carbon mineralization to warming and labile carbon input - Qiong Xiao; Wenju Zhang; Lei Wu; Yaping Huang; Zejiang Cai; Dongchu Li; Xingliang Xu; Iain P. Hartley (Journal of Environmental Management, 2024)

On-site smartphone detection of ethanol content using paper-based colorimetric polydiacetylene sensor arrays - Dong-En Wang; Changhan Yan; Sirui Bai; Yaping Zhang; Wenjing Huo; Kaiting Ning; Lei Zhao; Hui Yang; Huiyun Xu (Chemical Engineering Journal, 2024)

Nanocellulose based ultra-elastic and durable foams for smart packaging applications - Yang Liu; Yaping Zhu; Zijun Xu; Xin Xu; Pan Xue; Hong Jiang; Zhengjian Zhang; Meng Gao; Hongbin Liu; Bowen Cheng (Carbohydrate Polymers, 2024)

Establishment of an efficient callus transient transformation system for Vitis vinifera cv. ‘Chardonnay’ - Jieping Wu; Junxia Zhang; Xinyi Hao; Kai Lv; Yaping Xie; Weirong Xu (Protoplasma, 2024)

N-cycle gene abundance determination of N mineralization rate following re-afforestation in the Loess Plateau of China - Yaping Zhao; Yuqing Zhao; Shuohong Zhang; Yulin Xu; Xinhui Han; Gaihe Yang; Chengjie Ren (Soil Ecology Letters, 2024)

Baicalin − 2- ethoxyethyl ester alleviates renal fibrosis by inhibiting PI3K/AKT/NF-κB signaling pathway - Jiacun Li; Ke Zhang; Mei Xu; Huanyue Cui; Yaping Guo; Dahong Yao; Wenhua Chen; Huaimin Liang; Hangyu Wang; Jinhui Wang (Toxicology and Applied Pharmacology, 2024)

Engineered nanomaterials display a variable interaction with anoxygenic photoelectrogenic biofilm for pharmaceutical pollutants degradation - Ronghui He; Xubin Zhang; Jian Sun; Xiaoyan Bai; Qintie Lin; Yong Yuan; Yaping Zhang; Kang Dai; Zhenbo Xu (Chemical Engineering Journal, 2024)

A Review of Electrochemical Treatment Processes of Leachate Membrane Concentrate - Peixin Tang; Xu Ren; Zhicheng Pan; Meng Shen; Danni Peng; Yucheng Liu; Yaping Zhong; Yumei Peng; Xin Peng (Water, Air, & Soil Pollution, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Functional characterization of polyol/monosaccharide transporter 1 in Lotus japonicus - Leru Liu; Shaoming Xu; Lu Tian; Xuelian Qin; Guojiang Wu; Huawu Jiang; Yaping Chen (Journal of Plant Physiology, 2024)

Selective recovery of lithium from high-aluminum fly ash by using alkali-dissolution-assisted HBTA–TOPO synergistic extraction - Mingfei Xing; Fan Zhang; Pengyong Zheng; Yaping Wang; Li Zhao; Chuanyang Xu (Journal of Cleaner Production, 2024)

Infection of postharvest pear by Penicillium expansum is facilitated by the glycoside hydrolase (eglB) gene - Meiqiu Xu; Esa Abiso Godana; Jingyu Li; Yaping Deng; Yufei Ma; Huiyuan Ya; Hongyin Zhang (International Journal of Food Microbiology, 2024)

Identification and analysis of alleles in the aroma biosynthesis pathways based on Camellia sinensis ‘Jinguanyin’ haplotype-resolved genomes - Mengya Gu; Ting Gao; Mengting Xu; Yaping Hong; Yibin Wang; Jiaxin Yu; Yuhang Zhang; Wenqin She; Pengjie Wang; Naixing Ye (Trees, 2023)

Unprecedented early summer warming recorded in tree rings on the central eastern Tibetan Plateau over the past three centuries - Jiangfeng Shi; Hui Wang; Jinbao Li; Shiyuan Shi; Jiarui Xu; Yaping Zhang; Huayu Lu (Climate Dynamics, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Comparison of gap-filling methods for producing all-weather daily remotely sensed near-surface air temperature - Yaping Mo; Yongming Xu; Yonghong Liu; Yan Xin; Shanyou Zhu (Remote Sensing of Environment, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Noncovalent co-assembly of aminoglycoside antibiotics@tannic acid nanoparticles for off-the-shelf treatment of pulmonary and cutaneous infections - Guang Yang; Changrong Wang; Yaping Wang; Xiaoqing Liu; Ye Zhang; Ming Xu; Hongzhang Deng; Weiwei Wang (Chemical Engineering Journal, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

Manuring improves soil health by sustaining multifunction at relatively high levels in subtropical area - Xin Li; Lei Qiao; Yaping Huang; Dongchu Li; Minggang Xu; Tida Ge; Jeroen Meersmans; Wenju Zhang (Agriculture, Ecosystems & Environment, 2023)

Dual-emitting cellulose nanocrystal hybrid materials with circularly polarized luminescence for anti-counterfeiting labels - Lingxiao Xing; Guihua Li; Yaping Sun; Xu Wang; Zaiwu Yuan; Yingjuan Fu; Menghua Qin (Carbohydrate Polymers, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Ecological risk assessment of potentially toxic elements in selenium-rich soil with different land-use types - Jinming Zhang; Wen Ge; Chen Xing; Yuan Liu; Xiaofei Shen; Bing Zhao; Xinyu Chen; Yaping Xu; Shoubiao Zhou (Environmental Geochemistry and Health, 2023)

Assessing climatic impact on transition from Neanderthal to anatomically modern human population on Iberian Peninsula: a macroscopic perspective - Konstantin Klein; Gerd-Christian Weniger; Patrick Ludwig; Christian Stepanek; Xu Zhang; Christian Wegener; Yaping Shao (Science Bulletin, 2023)

Design of bifunctional TiO2-SSZ-13 mixed supports for potassium-resistant vanadia catalysts for NH3-SCR - Xuesong Liu; Yaping Yang; Jiaying Li; Yang Gao; Kaihao Fan; Yanghui Wang; Xintao Xu; Letong Yang; Xiaodong Wu (Fuel, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

Mapping nighttime PM2.5 concentrations in Nanjing, China based on NPP/VIIRS nighttime light data - Huijuan Chen; Yongming Xu; Sheng Zhong; Yaping Mo; Shanyou Zhu (Atmospheric Environment, 2023)

The association between organophosphate esters exposure and body mass index in children and adolescents: The mediating effect of sex hormones - Yaping Li; Liqin Hu; Bin Zhou; Zhiyi Zheng; Qitong Xu; Jun Liu; Lulu Song; Youjie Wang; Surong Mei (Chemosphere, 2023)

Enhanced arsenite removal from water using zirconium-ferrocene MOFs coupled with peroxymonosulfate:oxidation and multi-sites adsorption mechanism - Zongchen Li; Shengjia Ma; Linfeng Sang; Guojuan Qu; Tao Zhang; Bin Xu; Wei Jin; Yaping Zhao (Chemosphere, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Coordination polysaccharide nanomissiles with size/charge dual-transformability and immunomicroenvironment-reeducating activity potentiate PD-1 blockade in hepatocellular carcinoma - Yaping Wang; Junmin Qian; Weijun Xu; Guanghui Hou; Kunkun Zhao; Jinlei Wang; Wei Wang; Aili Suo (Chemical Engineering Journal, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Effects of low-protein-high-starch diet on growth performance, glucose and lipid metabolism of Amur sturgeon (Acipenser schrenckii) during feeding and starvation phases - Xiaoran Zhang; Yaping Zhu; Hongcheng Wei; Xu Gu; Xiufeng Wu; Min Xue; Xiaofang Liang (Aquaculture, 2023)

A high-efficiency mixotrophic photoelectroactive biofilm reactor (MPBR) for enhanced simultaneous removal of nutrients and antibiotics by integrating light intensity regulation and microbial extracellular electron extraction - Xinyuan Yao; Jian Sun; Xiaoyan Bai; Yong Yuan; Yaping Zhang; Yanbin Xu; Guofu Huang (Journal of Environmental Management, 2023)

Strict rule-based automatic training data extraction using Mobile laser scanning in urban area - Zhenyu Ma; Sander Oude Elberink; Yaping Lin; Panpan Xu; Binbin Xiang; Barbara Koch; Holger Weinacker (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Impact of green credit policy on sustainability performance of high-pollution enterprises - Yan Jiang; Shuyue Qin; Yaping Xu (Environmental Science and Pollution Research, 2022)

Carbon emission model of vehicles driving at fluctuating speed on highway - Yaping Dong; Jinliang Xu; Jie Ni (Environmental Science and Pollution Research, 2022)

The behavior of REEs indicates the dolomite petrogenesis and a unique dolomitization model of the Middle Permian Qixia formation in Northwest Sichuan Basin, China - Shengyang Xie; Xingzhi Wang; Bo Li; Long Wen; Liang Xu; Yao Du; Lin Xie; Yong Li; Yaping Wang; Yawen Li (Carbonates and Evaporites, 2022)

Enhancement of oral bioavailability and anti-hyperuricemic activity of aloe emodin via novel Soluplus®—glycyrrhizic acid mixed micelle system - Feng Shi; Lin Chen; Yaping Wang; Jing Liu; Michael Adu-Frimpong; Hao Ji; Elmurat Toreniyazov; Qilong Wang; Jiangnan Yu; Ximing Xu (Drug Delivery and Translational Research, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Tracking historical storm records from high-barrier lagoon deposits on the southeastern coast of Hainan Island, China - Liang Zhou; Xiaomei Xu; Yaping Wang; Jianjun Jia; Yang Yang; Gaocong Li; Changliang Tong; Shu Gao (Acta Oceanologica Sinica, 2021)

Long-term manuring increases microbial carbon use efficiency and mitigates priming effect via alleviated soil acidification and resource limitation - Qiong Xiao; Yaping Huang; Lei Wu; Yanfang Tian; Qiqi Wang; Boren Wang; Minggang Xu; Wenju Zhang (Biology and Fertility of Soils, 2021)

Spatio-temporal analysis of urban air pollutants throughout China during 2014–2019 - Chenkai Zhao; Ying Sun; Yaping Zhong; Senhao Xu; Yue Liang; Shu Liu; Xiaodong He; Jinghai Zhu; Takayuki Shibamoto; Miao He (Air Quality, Atmosphere & Health, 2021)

Exosomes derived from astrocytes after oxygen-glucose deprivation promote differentiation and migration of oligodendrocyte precursor cells in vitro - Yaping Xu; Yeye Tian; Yao Wang; Li Xu; Guini Song; Qiao Wu; Wei Wang; Minjie Xie (Molecular Biology Reports, 2021)

The influence of VDR polymorphisms on the type 2 diabetes susceptibility in Chinese: an interaction with hypertriglyceridemia - Dongdong Zhang; Cheng Cheng; Yan Wang; Yuan Xue; Yaping Liu; Yiming Liu; Mingming Feng; Ze Xu; Wenjie Li; Xing Li (Molecular Genetics and Genomics, 2021)

A 2-step algorithm combining glutamate dehydrogenase and nucleic acid amplification tests for the detection of Clostridioides difficile in stool specimens - Chengcheng Liu; Chenjie Tang; Yaping Han; Yuqiao Xu; Fang Ni; Ke Jin; Genyan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Leaching Behaviour and Enhanced Phytoextraction of Additives for Cadmium-Contaminated Soil by Pennisetum sp. - Fangzhou Li; Yaping Zhang; Shefeng Hao; Weiwei Xu; Kai Shen; Zhen Long (Bulletin of Environmental Contamination and Toxicology, 2020)

Solar UV radiation exacerbates photoinhibition of a diatom by antifouling agents Irgarol 1051 and diuron - Rui Hou; Yaping Wu; Juntian Xu; Kunshan Gao (Journal of Applied Phycology, 2020)

Identification of Potential Biomarkers with Diagnostic Value in Pituitary Adenomas Using Prediction Analysis for Microarrays Method - Hu Peng; Yue Deng; Longhao Wang; Yin Cheng; Yaping Xu; Jianchun Liao; Hao Wu (Journal of Molecular Neuroscience, 2019)

Population distribution patterns and changes in China 1953–2010 - Cuiling Liu; Yaping Xu; Fahui Wang (Journal of Geographical Sciences, 2019)

Analyzing Population Density Disparity in China with GIS-automated Regionalization: The Hu Line Revisited - Fahui Wang; Cuiling Liu; Yaping Xu (Chinese Geographical Science, 2019)

Enhanced Phytoextraction for Co-contaminated Soil with Cd and Pb by Ryegrass (Lolium perenne L.) - Yaping Zhang; Fangzhou Li; Weiwei Xu; Jinghua Ren; Sihui Chen; Kai Shen; Zhen Long (Bulletin of Environmental Contamination and Toxicology, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

The Resveratrol Alleviates the Hepatic Toxicity of CuSO4 in the Rat - Yaping Tian; Bing Wu; Xiaoping Li; Xuefei Jin; Fuqiang Zhang; Chunyan Jiang; Wenzhou Xu; Hang Li; Heyuan Wang (Biological Trace Element Research, 2019)

Probiotics decrease depressive behaviors induced by constipation via activating the AKT signaling pathway - Nana Xu; Wenting Fan; Xiaoyan Zhou; Yaping Liu; Ping Ma; Suhua Qi; Bing Gu (Metabolic Brain Disease, 2018)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Spatial and temporal precipitation patterns characterized by TRMM TMPA over the Qinghai-Tibetan plateau and surroundings - Ziqiang Ma; Yaping Xu; Jie Peng; Qiuxiao Chen; Dan Wan; Kang He; Zhou Shi; Hongyi Li (International Journal of Remote Sensing, 2018)

Rational Design and Cyclization of MIG6 Peptide to Restore its Binding Affinity for ErbB Family Receptor Tyrosine Kinases - Dingwa Zhang; Deyong He; Ling Huang; Yaping Xu; Lijun Liu (International Journal of Peptide Research and Therapeutics, 2018)

Molecular cytogenetic and genomic analyses reveal new insights into the origin of the wheat B genome - Wei Zhang; Mingyi Zhang; Xianwen Zhu; Yaping Cao; Qing Sun; Guojia Ma; Shiaoman Chao; Changhui Yan; Steven S. Xu; Xiwen Cai (Theoretical and Applied Genetics, 2018)

A novel homozygous complex deletion in CFTR caused cystic fibrosis in a Chinese patient - Keqiang Liu; Yaping Liu; Xue Li; Kai-Feng Xu; Xinlun Tian; Xue Zhang (Molecular Genetics and Genomics, 2017)

Genome-wide analysis of the terpene synthase gene family in physic nut (Jatropha curcas L.) and functional identification of six terpene synthases - Wangdan Xiong; Pingzhi Wu; Yongxia Jia; Xiaoyi Wei; Liangxiong Xu; Yanfang Yang; Deyou Qiu; Yaping Chen; Meiru Li; Huawu Jiang; Guojiang Wu (Tree Genetics & Genomes, 2016)

Expression Profiles of SIRT1 and APP Genes in Human Neuroblastoma SK-N-SH Cells Treated with Two Epigenetic Agents - Yaping Hou; Fanghua Wang; Linping Cheng; Tao Luo; Jie Xu; Huaqiao Wang (Neuroscience Bulletin, 2016)

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

Tolerance, oxygen consumption and ammonia excretion of Ophiopholis sarsii vadicola in different temperatures and salinities - Jinghui Fang; Jihong Zhang; Zengjie Jiang; Xuewei Zhao; Xu Jiang; Meirong Du; Yaping Gao; Jianguang Fang (Journal of Ocean University of China, 2015)

Trends of subtype variation of human immunodeficiency virus type 1 in Zhejiang Province, China - Yaping Yao; Ruolei Xin; Jiezhe Yang; Yun Xu; Jiafeng Zhang; Yan Xia; Xiaohong Pan; Zhihong Guo; Yanhui Song (Virus Genes, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Development of 39 novel polymorphic microsatellite markers for the giant mottled eel Anguilla marmorata and cross-amplification in other eel species - Xiaolu Wang; Fang Xu; Li Li; Yaping Zhang; Yandong Ding; Xue Zang; Yihe Jia; Guosong Zhang; Yayuan Wang; Xiaojun Wang; Hongwei Zhang; Shaowu Yin (Conservation Genetics Resources, 2014)

Anti-MS4a4B treatment abrogates MS4a4B-mediated protection in T cells and ameliorates experimental autoimmune encephalomyelitis - Yaping Yan; Zichen Li; Guang-Xian Zhang; Mark S. Williams; Gregory B. Carey; Jianke Zhang; Abdolmohamad Rostami; Hui Xu (Apoptosis, 2013)

Gender Differences in Preattentive Processing of Facial Expressions: An ERP Study - Qiang Xu; Yaping Yang; Pei Wang; Gang Sun; Lun Zhao (Brain Topography, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Enlargement of anode for enhanced simultaneous azo dye decolorization and power output in air-cathode microbial fuel cell - Jian Sun; Youming Li; Yongyou Hu; Bin Hou; Qian Xu; Yaping Zhang; Sizhe Li (Biotechnology Letters, 2012)

Cyanobacteria-blooming water samples from Lake Taihu induce endoplasmic reticulum stress in liver and kidney of mice - Wendi Qin; Liuyan Yang; Xuxiang Zhang; Zongyao Zhang; Lizhi Xu; Jun Wu; Jing An; Yaping Wang (Ecotoxicology, 2012)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)

Determination of Paracetamol Based on its Quenching Effect on the Photoluminescence of CdTe Fluorescence Probes - Li Li; Yaxiang Lu; Yaping Ding; Yu Cheng; Wanchen Xu; Fenfen Zhang (Journal of Fluorescence, 2012)

Analysis and evaluation of the source of heavy metals in water of the River Changjiang - Lan Wang; Yaping Wang; Chunxue Xu; Ziyi An; Suming Wang (Environmental Monitoring and Assessment, 2011)

Novel parvovirus sublineage in the family of Parvoviridae - Fang Wang; Yongwei Wei; Chun Zhu; Xianbo Huang; Yaping Xu; Lian Yu; Xuping Yu (Virus Genes, 2010)

Znrg, a novel gene expressed mainly in the developing notochord of zebrafish - Yaping Zhou; Yan Xu; Jianzhen Li; Yao Liu; Zhe Zhang; Fengjiao Deng (Molecular Biology Reports, 2010)

The application of geostatistics in grain size trend analysis: A case study of eastern Beibu Gulf - Fei Ma; Yaping Wang; Yan Li; Changjiang Ye; Zhiwei Xu; Fan Zhang (Journal of Geographical Sciences, 2010)

Design of Two Pyrazole-Based Sensors with Similar Configuration and Different Fluorescent Response to Anions - Yaping Li; Jie Shao; Xudong Yu; Xiufang Xu; Hai Lin; Zunsheng Cai; Huakuan Lin (Journal of Fluorescence, 2010)

Urinary Arsenic Speciation and its Correlation with 8-OHdG in Chinese Residents Exposed to Arsenic Through Coal Burning - Xin Li; Jingbo Pi; Bing Li; Yuanyuan Xu; Yaping Jin; Guifan Sun (Bulletin of Environmental Contamination and Toxicology, 2008)

Maternal cigarette smoking, metabolic gene polymorphisms, and preterm delivery: new insights on G×E interactions and pathogenic pathways - Hui-Ju Tsai; Xin Liu; Karen Mestan; Yunxian Yu; Shanchun Zhang; Yaping Fang; Colleen Pearson; Katherin Ortiz; Barry Zuckerman; Howard Bauchner; Sandra Cerda; Phillip G. Stubblefield; et al. (Human Genetics, 2008)